KAJIAN PENDAPATAN PENGELOLAAN WADUK BATU BESI PLTA KAREBBE, SOROWAKO-LUWU TIMUR, SULAWESI SELATAN - Sari, Andi Kartini (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2016)
Batu Besi Reservoir in the Luwu Timur Sulawesi Selatan Regency has been operated since January, 1988 and played significant role in determining the success of water resources utilization as Water Power Generation Plant (PLTA). Daily Inflow entering the reservoir is the record made at AWLR PT. INCO station from 1988 to 2004 with inundation and catchment area width of 585 km2 and 2,477 km2, effective and dead volumes of 1,938.86 MCM and 169.70 MCM, or 2,108.56 MCM in gross volume. Reservoir bin is utilized to fulfill the operational need of PT. INCO, a nickel mining company , in processing the nickel ore.Up to now, the objectives of water resource infrastructure, especially reservoir, are to supply electricity needed by the company to process the nickel ore and to achieve the reservoir autonomy. Such management is expected to give capability in financing the reservoir operational and maintenance in order to give direct income contribution to to regional government. All constraints, parameters and related variables consisted in the reservoir system should be calculated as much as possible in determining the reservoir operational guide, therefore, water resources can be utilized effectively and efficiently for fulfilling the company needs.PLTA Karebbe is the third water power generation plant, with 90 MW capacity, owned by PT. Internasional Nickel Indonesia (INCO), which is located in Larona Rive,. Up to the third quarter of 2009, the Karebbe project has reached 23% and expected to be finished 2012 and started for operation in mid 2012. The study of Batu Besi reservoir pattern in PLTA Karebbe for 37 years ahead of development and management consists of income analysis from the reservoir management. It is calculated using multiplication of water released into the reservoir with unit price of electricity tariff of each demand in order to calculate the electricity monthly use and income gained by PT.INCO for the last 37 years ahead (1998-2035). The amount of power released is significantly dependent to debit and effective pressure height in the reservoir. Every reservoir cost since the beginning of operation is calculated that includes the amount of income gained and the reservoir maintenance and operational costs. Annual average income due to reservoir water utilization in increasing the nickel productivity is Rp 619.467,864 per Kwh with total income of Rp.23.539.778,855 per Kwh and total electricity use of 69.631 Gwh.